The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/anti.12152
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure Nation: State Space, Hegemony, and Hydraulic Regionalism in Pakistan

Abstract: Large-scale infrastructures are often understood by state planners as fulfilling a national integrative function. This paper challenges the idea of infrastructures as national integrators by engaging theories of state/nation formation and infrastructure in a postcolonial context. Specifically, I put Lefebvre's characterization of the production of state space as a homogenization-differentiation dialectic in conversation with Gramsci's understanding of hegemony, bureaucracy, and nationalism to analyze the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 25 publications
0
56
0
1
Order By: Relevance
“…Although infrastructure in various forms have existed for millennia, the intersection of economic requirements, technical expertize and political incentives to create standardized structures for the purpose of consolidating state power and integrating nation is a modern phenomenon (Knox and Harvey, 2012, p. 523). In other words, infrastructure is increasingly understood as a means to gain legitimacy; to create an 'integrated' national space and ideology (Anwar, 2015;Goswami, 2004;Akhter, 2015;Harvey, 2012, 2015).…”
Section: Cpec As State-spacementioning
confidence: 99%
See 2 more Smart Citations
“…Although infrastructure in various forms have existed for millennia, the intersection of economic requirements, technical expertize and political incentives to create standardized structures for the purpose of consolidating state power and integrating nation is a modern phenomenon (Knox and Harvey, 2012, p. 523). In other words, infrastructure is increasingly understood as a means to gain legitimacy; to create an 'integrated' national space and ideology (Anwar, 2015;Goswami, 2004;Akhter, 2015;Harvey, 2012, 2015).…”
Section: Cpec As State-spacementioning
confidence: 99%
“…He argues that nationbuilding, economic reconstruction efforts and provision of large dams and other river infrastructures have been closely tied together in the case of Pakistan (Akhter, 2015). Indus Water Treaty, signed on 19 September 1960, divided the control over Indus River and its tributaries among India and Pakistan.…”
Section: Cpec As State-spacementioning
confidence: 99%
See 1 more Smart Citation
“…Within this reading, rivers cease to be simple flows of water but are socially‐produced objects that are made and remade through power‐laden socio‐political and technical interaction (Swyngedouw, ). Previous research has shown how the construction of infrastructure, such as dams, becomes articulated within storylines that assert the infrastructure's symbolism as representative of both nationalism and state‐building (Akhter, ; Menga, ; Mitchell, ; Mossallam, ). For example, Kaika (2006) has explored the construction of the Marathon Dam, built in the 1920s, arguing that the project's neoclassical ornamentation represented the construction of parallels between Athens’ modernisation and the successes of Ancient Greek civilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Attention to scalar difference is a key methodological principle undergirding my analysis, as indeed it is for many water geographers (Akhter ; Harris and Alatout ; Mustafa ; Swyngedouw ). Geographers have examined the spatiality of water expertise, the shifting sites of authoritative knowledge production, and the role of regional political economy, in several contexts, including stream restoration (Lave ), the representation of watersheds and rivers (Cohen and Bakker ; Harris and Alatout ; Hwang ; Sneddon and Fox ; Swyngedouw ) and the global circulation of irrigation expertise (Akhter and Ormerod ).…”
Section: Introductionmentioning
confidence: 99%